Weltkarte in Nordpolar-Sternprojektion nach einer Idee von Dr. G. JaÌˆger, in Wien. - Petermann, A. (August), 1822-1878 (Justus Perthes, 1865)
Map shows six continents, major cities, and the trans-Atlantic cable with the north pole at the center of the map; the northern hemisphere as a full circle and the southern hemisphere in sections. Scale [1:185,000,000].